Oral Health and Hospital Infections: A Scope Review of the Performance of Dentists in Intensive Care Units - Thyago Oliveira Cardoso; Áurea Luz Felícia Marques Miécimo da Silva; Marcelo Ferreira da Silva; Sirlei Moura de Almeida Maggioni; Celso Oliveira de Sousa; Flávio Rodrigues Ferreira Alves (The Open Dentistry Journal, 2026)
Introduction Oral health plays a crucial role in preventing hospital-acquired infections, particularly among critically ill patients admitted to Intensive Care Units (ICUs). In these environments, the oral cavity may act as a reservoir for pathogenic microorganisms capable of triggering systemic infections such as ventilator-associated pneumonia and sepsis. Objective This study aimed to analyze the available scientific evidence on the role of dentists in preventing hospital infections in ICU patients and to evaluate the impact of hospital dentistry interventions on clinical outcomes. Methods This scoping review was conducted based on a search of PubMed, SciELO, and Google Scholar databases, following the steps of identification, screening, and eligibility of studies. Titles, abstracts, and full texts were reviewed by two independent reviewers, with a third reviewer resolving disagreements. Ten studies were selected, ranging from observational evaluations to clinical trials and quasi-experimental studies, involving hospitalized adult, pediatric, and convalescent patients. Results The included studies showed that dental interventions were associated with reduced respiratory infections, especially ventilator-associated pneumonia, along with lower systemic complications and hospital mortality. Discussion The evidence highlights the importance of integrating dentists into multidisciplinary ICU teams to strengthen infection prevention strategies and improve patient safety through structured oral health protocols. Conclusion The inclusion of dentists in ICUs is essential for preventing hospital infections and improving clinical outcomes, reinforcing the need for standardized protocols, specialized training, and public policies supporting hospital dentistry.